2008
DOI: 10.1038/onc.2008.167
|View full text |Cite
|
Sign up to set email alerts
|

Chfr interacts and colocalizes with TCTP to the mitotic spindle

Abstract: Chfr is a checkpoint protein that plays an important function in cell cycle progression and tumor suppression, although its exact role and regulation are unclear. Previous studies have utilized overexpression of Chfr to determine the signaling pathway of this protein in vivo. In this study, we demonstrate, by using three different antibodies against Chfr, that the endogenous and highly overexpressed ectopic Chfr protein is localized and regulated differently in cells. Endogenous and lowly expressed ectopic Chf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
41
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 28 publications
6
41
2
Order By: Relevance
“…TCTP binding to the spindle, predominantly to the poles, has since been confirmed by reports from other laboratories [17,18]. It is anticipated that TCTP is involved in stabilising spindle microtubules [17,19], and the observed detachment of TCTP from the spindle might be important for the metaphase-anaphase transition. We also observed that TCTP is subject to mitotic phosphorylation (M. Lee, Y. Gachet and U.A.…”
Section: ++ -Binding Proteinsupporting
confidence: 52%
See 1 more Smart Citation
“…TCTP binding to the spindle, predominantly to the poles, has since been confirmed by reports from other laboratories [17,18]. It is anticipated that TCTP is involved in stabilising spindle microtubules [17,19], and the observed detachment of TCTP from the spindle might be important for the metaphase-anaphase transition. We also observed that TCTP is subject to mitotic phosphorylation (M. Lee, Y. Gachet and U.A.…”
Section: ++ -Binding Proteinsupporting
confidence: 52%
“…Burgess et al [17] demonstrated that lowly expressed ectopic Chfr is localised in the cytoplasm, but localises to the spindle during mitosis. They also showed that Chfr interacts with TCTP throughout the cell cycle, unless cells are treated with microtubule-destabilising agents.…”
Section: • Tctp As a General Mitotic Regulatormentioning
confidence: 99%
“…In later studies, TCTP phosphorylation has even been exploited as a marker for Plk-1 activity (Cucchi et al 2010) and as a potential prognostic marker in testing the efficacy of anticancer drugs (Lucibello et al 2015). Localisation of TCTP to the mitotic spindle, particularly the spindle poles, was also reported by other laboratories (Jaglarz et al 2012;Burgess et al 2008;Bazile et al 2009). A very recent paper even demonstrated the importance of TCTP for the meiotic spindle in mouse oocytes (Jeon et al 2016).…”
Section: Tctp a Microtubule Stabilising Protein At The Mitotic And Tmentioning
confidence: 80%
“…TCTP/tpt1 was discovered in Ehrlich ascite tumor cells 48 and characterized as a histamine-releasing factor. [49][50][51] TCTP/tpt1 has been shown to regulate the cytoskeleton 52,53 and protein synthesis 22 and inhibit apoptosis. 11,12,20,[54][55][56][57] Our findings are consistent with previous studies which have demonstrated that down regulation of TCTP/tpt1 can induce tumor reversion.…”
Section: Discussionmentioning
confidence: 99%